An Analysis of Code Mixing and Code Switching Used in Maudy Ayunda's YouTube Channel Video - Lestari, Ni Putu Diana Eka; Artini, Luh Putu; Sri Adnyani, Ni Luh Putu (Institut Agama Islam Negeri Palopo, 2025)
The phenomenon of code mixing and code switching takes place in bilingual or multilingual societies. These phenomena occur not only in direct communication but also virtually on social media platforms, such as YouTube. This study was grounded in the theoretical frameworks of Hoffman (1991), who identifies three distinct types of code mixing: intra-sentential code mixing, intra-lexical code mixing, and code-mixing involving pronunciation change. Meanwhile, types of code switching are classified into tag switching, intra-sentential code switching, and inter-sentential code switching (Wei, 2007). This study analyzed the types of code mixing and switching used in one of Maudy Ayunda's YouTube Channel videos entitled